Marginality, Co-Integration and Change: Social History as a Critical Exercise - Bouchard, Gérard (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractIn an address delivered as a guest speaker, Gérard Bouchard conveys the theoretical and historiographical considerations which led to the writing of his Quelques arpents d'Amérique. In particular, he presents the concept of family reproduction as a promising tool towards the understanding of the links between micro and macro social phenomena. Thereafter, he traces the limits of the notion of marginality for the study of the multiple economic activities of the Saguenay, which he rejects in favour of co-integration and integration. These concepts allow a consideration of the relation between two systems and for the autonomous dynamic of the society otherwise called a periphery. As illustrations of his global approach, he then offers some conclusions pertaining to contraception, agricultural change and education. He proceeds to identify elements of other North American historiographies of agricultural regions, in Quebec, Canada and the United States, which call for the use of the notion of co-integration. Only once detailed comparisons are made will historians be able to discriminate between the originality of the French Canadian habitant and his “Americanity”.